2008
DOI: 10.1182/blood-2007-10-115659
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic recovery in survivors following chemotherapy for AIDS-related non-Hodgkin lymphoma

Abstract: The late effects of chemotherapy on immunologic parameters in AIDS-related non-Hodgkin lymphoma (NHL) have not been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…No significant detrimental effects on underlying HIV infection were noticed. The effect on CD4 cell count and HIV viral load does not seem superior than what is usually seen as a consequence of standard CT given with concomitant HAART [27][28][29] ; within the first year after transplantation the CD4 count reached a higher level than the baseline, and the HIV viremia remained undetectable in most patients. Of note is that no patients receiving transplant died because of treatment-related toxicity, infections, or other HIVrelated complications.…”
Section: Discussionmentioning
confidence: 72%
“…No significant detrimental effects on underlying HIV infection were noticed. The effect on CD4 cell count and HIV viral load does not seem superior than what is usually seen as a consequence of standard CT given with concomitant HAART [27][28][29] ; within the first year after transplantation the CD4 count reached a higher level than the baseline, and the HIV viremia remained undetectable in most patients. Of note is that no patients receiving transplant died because of treatment-related toxicity, infections, or other HIVrelated complications.…”
Section: Discussionmentioning
confidence: 72%
“…SC-EPOCH-RR had significantly less immune toxicity than da-EPOCH, which was administered for 6 cycles, and achieved excellent immune reconstitution and HIV control after reinstitution of cART, similar to those findings when chemotherapy is administered with cART. 23 The survival outcomes compare favorably with da-EPOCH, whereby PFS and OS were 73% and 60%, respectively, at 53 months, suggesting dose-dense rituximab may be beneficial, although the study was not designed to address this question. 7 Our results appear to be significantly better than those achieved in a phase 3 study of CHOP with or without rituximab, which reported 50% time to progression (comparable with PFS in the present study) and OS with rituximab plus CHOP at 2.4 years.…”
Section: Org Frommentioning
confidence: 93%
“…It should be noted, however, that in a study of infusional chemotherapy (without rituximab) for AIDS-NHL combined with antiretroviral therapy, in which 68 patients survived more than 3 months, two of the surviving patients developed KS. 34 Thus, the decrease in KSHV identified in this study notwithstanding, it should not be presumed that lymphoma chemotherapy without rituximab confers protection against the development of KS. Indeed, there are a series of reports of KS exacerbation or de novo occurrence in HIVinfected patients with Castleman disease who were treated with rituximab.…”
Section: Wwwjcoorgmentioning
confidence: 98%